2011
DOI: 10.2337/db10-1592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Hypoglycemia on Human Cerebral Glucose Metabolism Measured by 13C Magnetic Resonance Spectroscopy

Abstract: OBJECTIVETo investigate the effect of acute insulin-induced hypoglycemia on cerebral glucose metabolism in healthy humans, measured by 13C magnetic resonance spectroscopy (MRS).RESEARCH DESIGN AND METHODSHyperinsulinemic glucose clamps were performed at plasma glucose levels of 5 mmol/L (euglycemia) or 3 mmol/L (hypoglycemia) in random order in eight healthy subjects (four women) on two occasions, separated by at least 3 weeks. Enriched [1-13C]glucose 20% w/w was used for the clamps to maintain stable plasma g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
2
23
1
Order By: Relevance
“…Indeed, measurement of glucose concentrations and calculation of glucose uptake rates revealed that control animals were limited by transport in their ability to take up sufficient amounts of glucose at a plasma glucose level of 2.5 mM to support normal TCA cycle function, which was not the case after exposure to antecedent recurrent hypoglycemia. This is in contrast to prior reports of healthy and type 1 diabetic humans that underwent a 13 C-glucose infusion during hypoglycemia, which did not exhibit a significant drop in TCA cycle activity under clamped hypoglycemia (36). However, based on differences in brain glucose concentration among these studies conducted in humans and our study one may have predicted this discrepancy in results: the brain glucose levels during hypoglycemia achieved in human controls and type 1 diabetic subjects of 0.5 and 0.6 μmol/g (37) are several times higher than the K m of hexokinase I (the major brain isozyme) for glucose (0.045-0.07 mM; refs.…”
Section: Discussioncontrasting
confidence: 54%
“…Indeed, measurement of glucose concentrations and calculation of glucose uptake rates revealed that control animals were limited by transport in their ability to take up sufficient amounts of glucose at a plasma glucose level of 2.5 mM to support normal TCA cycle function, which was not the case after exposure to antecedent recurrent hypoglycemia. This is in contrast to prior reports of healthy and type 1 diabetic humans that underwent a 13 C-glucose infusion during hypoglycemia, which did not exhibit a significant drop in TCA cycle activity under clamped hypoglycemia (36). However, based on differences in brain glucose concentration among these studies conducted in humans and our study one may have predicted this discrepancy in results: the brain glucose levels during hypoglycemia achieved in human controls and type 1 diabetic subjects of 0.5 and 0.6 μmol/g (37) are several times higher than the K m of hexokinase I (the major brain isozyme) for glucose (0.045-0.07 mM; refs.…”
Section: Discussioncontrasting
confidence: 54%
“…Although devoid of major effects in modeling 13 C data from short experiments where isotopic steady-state is not reached, the inclusion of V Gln and dilution from glutamine are crucial for reliable determination of V TCA and V X in one-compartment modeling. This model was employed in recent studies to estimate fluxes from 13 C curves of glutamate C4 and C3 (2528). …”
Section: One-compartment Model Of Brain Energy Metabolismmentioning
confidence: 99%
“…3 The cerebral response to hypoglycemia in the healthy brain involves changes in regional blood flow 4,5 and sequential adjustments in cerebral metabolism in order to provide sufficient fuel for brain activity. As the levels of glucose, the principal cerebral energy substrate, drop from 5 to B3 mmol/L in plasma, cerebral metabolic rate of glucose (CMRglc) and cerebral metabolic rate of oxygen (CMRO 2 ) are preserved [6][7][8] despite lower brain glucose uptake. 9 The brain starts using alternative fuels such as glycogen in this glycemic range.…”
Section: Introductionmentioning
confidence: 99%